Unintended consequences of framing a utility-value intervention in two-year colleges. (August 2019) - Canning, Elizabeth A.; Priniski, Stacy J.; Harackiewicz, Judith M.
Abstract: Utility-value (UV) writing interventions help students find the personal relevance of course material to promote interest and performance. However, little is known about how best to frame the intervention, particularly in the 2-year college context where students have more varied backgrounds than the samples previously studied. Using a randomized field experiment, we tested two ways of framing a UV writing intervention (student-framed vs. instructor-framed examples of UV), against a control assignment. Contrary to previous research, we found that students struggling in the course became less interested and perceived less utility value overall in UV conditions, compared to the control. The student-framed UV intervention made the course more interesting for students who were doing well in the course, but decreased grades for students struggling in the course, compared to the instructor-framed UV intervention. We examine psychological (e.g., confidence, engagement) and cognitive (linguistic indicators of cognitive processing) variables as mechanisms. Highlights: A utility-value intervention in 2-year colleges did not replicate previous research. Instructor-framed utility value examples had positive effects for some students. Peer-framed utility value examples had negative effects for low-achieving students.